Evaluasi Pemanfaatan Data Pos Hujan dan Data Satelit TRMM dalam Pemodelan Debit Sintetik DAS Temef - Donny Harisuseno; Sri Wahyuni; Davianto Frangky Welkis (Jurnal Teknik Sumber Daya Air, 2022)
Rainfall data collection based on the TRMM (Tropical Rainfall Measuring Mission) satellite provides a good alternative in estimating rainfall. TRMM technology can minimize manual rainfall recording errors and increase rainfall accuracy for hydrological analysis. From the results of the statistical relationship analysis, the most accurate results obtained are 9 years of calibration and 1 year of validation, the selected equation is a polynomial with the following equation y = 0.0112 x2 - 0.2564x + 4,1293, so that validation analysis is carried out with the selected equation so that the validation results are obtained against 1 year rainfall data for the RMSE value of 7.022. The NSE value is 0.923, the Correlation Coefficient is 0.94 and the relative error value is 5.48 and the results of the equation for discharge are modeling return periods of discharge 2, 5, 10, 20 and 25 years for discharge observations of 2 years return period; Q = 84.44, m3/s at 5 years return period; Q = 105.95 m3/s, 10 year return period; Q = 120.86 m3/s, 20 years return period; Q = 135.16 m3/s, 25 years return period; Q = 139.69 m3/s. Meanwhile, for the simulation discharge, the return period is 2 years; Q =51,84 m3/s at 5 year return period; Q = 65,35 m3/s, 10 year return period; Q = 74,15 m3/s, 20 years return period; Q = 84,89 m3/s, return period of 25 years; Q = 94,65 m3/s.